Design and Fabrication of Wear-Resistant Coatings Using Thermal Spray Techniques (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study focuses on the design and fabrication of wear-resistant coatings using advanced thermal spray techniques to enhance the surface durability of engineering components. Various coating materials, including ceramics, metallic alloys, and composite powders, were deposited onto substrate surfaces through controlled thermal spraying processes such as plasma spraying and high-velocity oxy-fuel (HVOF) spraying. The microstructural characteristics, adhesion strength, and wear resistance of the fabricated coatings were systematically evaluated under different operational conditions. Experimental results demonstrate that optimized thermal spray parameters significantly improve coating density, hardness, and resistance to abrasive and erosive wear, highlighting the potential of these coatings for extending the service life of critical industrial components. The results demonstrate that coating performance strongly depends on deposition technique and process parameters, with HVOF-sprayed composite coatings exhibiting superior density, adhesion, and wear resistance. This study presents a comparative parametric analysis of thermal spray techniques rather than a universal coating framework.